Short-term changes in chest CT images among individuals at low altitude after entering high-altitude environments - Wang, Peng; Zuo, Zhiwei; Wu, Jie; Wang, Jianxiong; Jiang, Rui; Du, Feizhou (Frontiers in Public Health, 2024)
Objective: To investigate the short-term changes in chest CT images of lowaltitude populations after entering a high-altitude environment.Methods: Chest CT images of 3,587 people from low-altitude areas were obtained within one month of entering a high-altitude environment. Abnormal CT features and clinical symptoms were analyzed.Results: Besides acute high-altitude pulmonary edema, the incidence of soft tissue space pneumatosis was significantly higher than that in low-altitude areas. Pneumatosis was observed in the mediastinum, cervical muscle space, abdominal cavity, and spinal cord epidural space, especially the mediastinum.In addition to acute high-altitude pulmonary edema, spontaneous mediastinal emphysema often occurs when individuals in low-altitude areas adapt to the high-altitude environment of cold, low-pressure, and hypoxia.When the gas escapes to the abdominal cavity, it is easy to be misdiagnosed as gastrointestinal perforation. It is also not uncommon for gas accumulation to escape into the epidural space of the spinal cord. The phenomenon of gas diffusion into distant tissue space and the mechanism of gas escape needs to be further studied.